2000
DOI: 10.1034/j.1399-3003.2000.16b11.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolic status in patients with severe COPD with and without long-term prednisolone

Abstract: Both abnormalities in high energy phosphate metabolism and a decreased oxidative enzyme capacity have been reported in skeletal muscle of stable chronic obstructive pulmonary disease (COPD) patients. The first aim of this study was to investigate whether these findings are present in anterior tibialis muscle and whether or not they are associated. Abnormalities in mitochondrial structure and function as well as signs of myopathy have been found during corticosteroid treatment. The second aim of this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
(37 reference statements)
2
18
0
5
Order By: Relevance
“…Previous studies indicated abnormal protein catabolism/anabolism [1][2][3]. Decreased oxidative capacity is observed in mitochondria [6,7] but this mechanism is yet controversial [17,18]. The present study demonstrated that serum lactate levels during exercise were significantly elevated in corticosteroid-treated patients.…”
Section: Discussionmentioning
confidence: 43%
“…Previous studies indicated abnormal protein catabolism/anabolism [1][2][3]. Decreased oxidative capacity is observed in mitochondria [6,7] but this mechanism is yet controversial [17,18]. The present study demonstrated that serum lactate levels during exercise were significantly elevated in corticosteroid-treated patients.…”
Section: Discussionmentioning
confidence: 43%
“…This might be sufficient to perform the biochemical and cellular analyses required for several purposes in COPD patients [25] and patients with neuromuscular disorders [12]. In addition, nutritional status did not appear to be a limitation to the microbiopsy technique.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to the vastus lateralis, the diaphragm of these patients is characterised by an increased oxidative capacity [7][8][9] and, strikingly, an augmented mitochondrial density was found when compared with healthy age-matched controls [6]. Similarly, since normal oxidative enzyme activities have been reported for COPD in another peripheral muscle, the tibialis anterior [10], a normal mitochondrial fractional area is anticipated in this muscle.…”
mentioning
confidence: 90%